Rhetorical Devices in Political Speeches: Nigel Farage’s Speeches at the European Parliament - Abdel-Hafiz Hussein, Ahmed Sokarno (Technium Social Sciences Journal, 2020)
Nigel Farage’s speeches and rhetoric have been instrumental and effective in the British voters’ decision to withdraw from the European Union. This paper aims to study rhetorical devices in the speeches of Nigel Farage at the European Parliament: list constructions, contrastive pairs etc. Having identified and classified the rhetorical devices, I proceed to perform a frequency analysis with the purpose of determining the number of times each device occurs. Thus the research questions are: (a) what rhetorical devices permeate the speeches? and (b) what is their frequency of occurrence? In order to achieve these objectives, I have studied twenty speeches Farage delivered at the European Parliament during the period from 2010 to 2017. I examine rhetorical devices that were previously treated as nonessential in Farage’s speeches (cf. Hädicke 2012) and I present arguments against the claim that the three-part list is the most common strategy in political speeches.